Tooth loss in aggressive periodontitis after active periodontal therapy: patient-related and tooth-related prognostic factors - Bäumer, Amelie; Pretzl, Bernadette; Cosgarea, Raluca; Kim, Ti-Sun; Reitmeir, Peter; Eickholz, Peter; Dannewitz, Bettina (Journal of clinical periodontology, 2011)
Bäumer A, Pretzl B, Cosgarea R, Kim T-S, Reitmeir P, Eickholz P, Dannewitz B. Tooth loss in aggressive periodontitis after active periodontal therapy: patient-related and tooth-related prognostic factors. J Clin Periodontol 2011; doi: 10.1111/j.1600-051X.2011.01733.x. Abstract Objectives: To assess prognostic factors for tooth loss after active periodontal therapy (APT) in patients with aggressive periodontitis (AgP) at tooth level. Material and methods: Eighty-four patients with AgP were re-evaluated after a mean period of 10.5 years of supportive periodontal therapy (SPT). Two thousand and fifty-four teeth were entered into the model. The tooth-related factors including baseline bone loss, tooth location and type, furcation involvement (FI), regenerative therapy, and abutment status, as well as time of follow-up and other patient-related factors were tested for their prognostic value at tooth level. Multilevel regression analysis was performed for statistical analysis to identify factors contributing to tooth loss. Results: During SPT, 113 teeth (1.34 teeth per patient) were lost. Baseline bone loss, use as abutment tooth, tooth type, and maxillary location contributed significantly to tooth loss during SPT. Molars showed the highest risk for tooth loss after APT. Moreover, time of follow-up and the patient-related factor “educational status” significantly accounted for tooth loss at tooth level. Conclusion: Baseline bone loss, abutment status, tooth location, and type as well as time of follow-up and educational status were detected as prognostic factors for tooth loss during SPT in patients with AgP at tooth level.